Imbalance in expression of hop (Humulus lupulus) chalcone synthase H1 and its regulators during hop stunt viroid pathogenesis - Füssy, Zoltán; Patzak, Josef; Stehlík, Jan; Matoušek, Jaroslav (Journal of plant physiology, 2013)
Viroid-derived small RNAs generated during hop stunt viroid (HSVd) pathogenesis may induce the symptoms found in the hop cultivar "Admiral", including observed shifts in phenylpropanoid metabolites and changes in petiole coloration. Using quantitative RT-PCR, we examined hop lupulin gland-specific genes that have been shown to be involved in phenylpropanoid metabolism, for altered expression in response to infection with two HSVd isolates, HSVd-g and CPFVd. Most notably, the expression of a gene encoding a key enzyme for phenylpropanoid synthesis, naringenin-chalcone synthase H1 (chs_H1), decreased up to 40-fold in infected samples. In addition, a marked decrease in the expression of HlbHLH2 and an increase in the expression of HlMyb3 were observed. These two genes encode transcription factors that form a ternary complex with HlWDR1 for chs_H1 promoter activation. In a transient expression assay, a decrease in the ternary complex potential to activate the chs_H1 promoter was observed upon the decrease of HlbHLH2 expression. In addition, targeting of the chs_H1 transcript by vd-sRNAs may contribute to these expression changes. Our data show that HSVd infection causes a significant imbalance in the expression of phenylpropanoid metabolite-affecting genes via a complex mechanism, possibly involving regulatory disorders and direct targeting by vd-sRNA.
Keywords: Gene Expression Regulation, Enzymologic; nemoci rostlin; regulace genové exprese enzymů; transkripční faktory; listy rostlin; Humulus; Up-Regulation; Plant Proteins; RNA, Viral; propanoly; Plant Stems; viroidy; Plant Leaves; upregulace; Transcription Factors; messenger RNA; RNA rostlin; polymerázová řetězová reakce s reverzní transkripcí; rostlinné proteiny; RNA virová; RNA, Messenger; RNA, Plant; Computational Biology; Down-Regulation; Reverse Transcriptase Polymerase Chain Reaction; Acyltransferases; Gene Expression Regulation, Plant; regulace genové exprese u rostlin; acyltransferasy; Plant Diseases; Viroids; RNA Interference; exprese genu; down regulace; RNA interference; výpočetní biologie; stonky rostlin; Gene Expression; Propanols